Stress and stress management of public elementary grades teachers selected schools Division of Pasig City and San Juan City - Abeja, Lydia C. (Manila : National University, 2007)
This research was limited to the one-hundred eight public elementary grades teachers from three schools in the Division of Pasig City and San Juan City.
Title Page -- Approval Sheet -- Acknowledgement -- Dedication -- Abstract -- Table of Contents -- List of Tables -- List of Figures -- Chapter 1: The Problem and its Setting -- Chapter 2: Review of Related Literature and Studies -- Chapter 3. Research Design and Methodology -- Chapter 4. Presentation, Analysis and Interpretation -- Chapter 5. Summary, Conclusions and Recommendations -- Bibliography -- Appendices -- Curriculum Vitae .
Research Method: Descriptive Design.
Includes bibliographical references.